Inadequate sound velocity profile measurement’s artifacts in multibeam echosounder system data - Mahmud, Mohd. Razali; Gunathilaka, M. D. E. K. (2008)

(untitled)
One of the most advanced and effective hydrographic survey technique is multibeam echosounder system. These systems use sound waves to measure the depths below the water surface. The final bathymetry is determined using the travel time of the acoustic pulse traveled between the transducer and the bottom surface, and the direction of each beam. The quality of the bathymetric data highly depends on the knowledge that one has about the medium that the signal travels through. Temperature, pressure and salinity are the dominant factors influencing the speed of sound in the water. These factors vary in both temporally and spatially; making this tasks a challenge. In a normal survey routine, one or two sound velocity profile (SVP) castes are made according to the desire of the hydrographer. Measuring the physical properties that control sound speed using Conductivity, Temperature and Depth (CTD) probe or direct sound speed measurements using a SVP probe is the standard procedure for collecting SVP’s. Bringing the vessel to halt, lowering the sensor and taking care of all the data quality assurance and data transferring would usually takes more than 30 minutes of ship time. Because of this, most hydrographic agencies are reluctant to take more frequent SVP’s. However the water mass really does change over the time, much shorter than this sampling interval. This variation in the SVP causes unknown propagation of the beams through the water column. Depth and positional uncertainties are the results of this issue. These uncertainties show up in digital terrain models of the bathymetry as ridges or valleys at the extreme swath areas; typically where the edges of adjacent swath overlap. Ridges or furrows that occurred depend on whether the actual refraction effect is greater or less than that of the measured SVP. These affects are discussed for flat array multibeam sonar systems using both synthetic and real data and compared against International Hydrographic Organization's (IHO) standards for hydrographic surveys.